Ultrasonic wave propagation in a layered medium under different boundary conditions - Aleksander PILARSKI (Archives of Acoustics)
This paper presents an analysis of the possibility of using the phase velocity measurements of surface or plate waves for the evaluation of the adhesive bond strength, i.e. of the adhesion degree in layered joints. Dispersive curves are determined for phase velocities in layer on base and layer on layer systems with two kinds of boundary conditions, i.e. welded and smooth ones, by numerical solutions of the characteristic equations. The procedure of deriving these equations for any number of layers is given.